Pengaruh Sistem Informasi dan Partisipasi Politik terhadap Efektivitas Pemilihan Kepala Daerah Serentak selama Pandemi COVID-19 - Afif Syarifudin Yahya; Andi Masrich; Karno Karno (Society, 2025)
The COVID-19 pandemic required new approaches to organizing regional elections, highlighting the use of information systems to reduce infection risk and improve election management effectiveness. This study examines the influence of information systems and political participation on the efficacy of simultaneous regional head elections during the pandemic. A quantitative design determined a sample of 402 respondents with the Slovin formula at a 95% confidence level. Data were collected through a Likert-scale questionnaire comprising 12 indicators of information systems, 21 of political participation, and 12 of electoral effectiveness, and analyzed using Structural Equation Modeling (SEM) with LISREL. The results show that information systems exerted a positive but statistically insignificant effect on electoral effectiveness (T-value = 0.79, below the 1.96 threshold). In contrast, political participation demonstrated a significant positive impact (T-value = 6.79), underscoring its decisive role in achieving effective election outcomes under pandemic conditions. These findings emphasize the importance of citizen engagement for sustaining democratic processes during public health crises and illustrate how digital technologies can support, but not replace, active political participation.